Occurrence and spatial variation of Anisakis pegreffii in the Atlantic horse mackerel Trachurus trachurus (Carangidae): A three-year monitoring survey in the western Ligurian Sea. (January 2022) - Menconi, Vasco; Pastorino, Paolo; Canola, Serena; Pavoletti, Elena; Vitale, Nicoletta; Scanzio, Tommaso; Righetti, Marzia; Mugetti, Davide; Tomasoni, Mattia; Bona, Maria Cristina; Prearo, Marino
Abstract: The Atlantic horse mackerel ( Trachurus trachurus ) is a commercially important fish species. Most parasitological studies on the anisakid nematodes occurrence in T. trachurus to date have involved fish from the Atlantic Ocean, while few studies are available for the Mediterranean Sea. Since T. trachurus is used raw and cooked in Ligurian cuisine (northwest Italy), assessment of possible consumer health risks (i.e., anisakiasis and allergic issues) is warranted. With this study we investigated the occurrence of zoonotic anisakid nematode larvae in the Atlantic horse mackerel. Between 2017 and 2019 a parasitological survey was carried out on 481 T. trachurus from four commercial fishing areas (Sanremo, n = 45; Imperia, n = 30; Savona, n = 300; Arenzano, n = 106) in the Ligurian Sea (western Mediterranean Sea). All isolated larvae morphologically assigned to the genus Anisakis (n = 937) were identified as A. pegreffii by PCR-RFLP. The total prevalence of A. pegreffii was 60.9% (95% confidence interval [CI] 56.5–65.3); the prevalence by area was: Savona (89.3%; 95% CI 85.8–92.8) > Imperia (20%; 95% CI 4.8–35.2) > Arenzano (16%; 95% CI 8.9–23.1) > Sanremo (4.4%; 95% CI 0–10.7). Anisakis pegreffii larvae were found in visceral organs (99.15%) and muscle tissue (0.85%). In addition, 411 larvae morphologically referable to the genus Hysterothylacium sp. were also isolated but only in the viscera. This parasitological survey provides new data on the occurrence and the level of anisakid nematode infection in the Atlantic horse mackerel. Highlights: The occurrence of anisakid nematode was investigated in Trachurus trachurus from the Ligurian Sea. A total of 937 larvae of Anisakis pegreffii were collected. The total prevalence of A. pegreffii was 60.9%. Savona showed the higher prevalence (89.3%) compared to the other areas. 411 larvae morphologically referable to the genus Hysterothylacium sp. were also isolated.